Light propagation in a GRIN microlens with gain or loss and comparison with lossless case - Lindlein, Norbert; et al. (Micro-Optics, VCSELs, and Photonic Interconnects II: Fabrication, Packaging, and Integration, 2006)
The correspondence between the linear integral transform and the ray-transfer matrix of a diffraction-free first-order optical system is used to describe the ray trajectory and to study the point spread function (PSF) in an active GRIN microlens characterized by a complex refractive index. The results show that the active microlens is regarded as a lossless microlens with a Gaussian mask induced by the complex refractive index. Comparison between light propagation effects in passive and active GRIN microlens is outlined.
Keywords: Active material; GRIN optics; PSF; Ray-tracing